2021
DOI: 10.17222/mit.2021.162
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF A HYBRID BIOCOMPOSITE OF HA/HDPE REINFORCED WITH MULTI-WALLED CARBON NANOTUBES (MWCNTs) AS A BONE-SUBSTITUTE MATERIAL

Abstract: In this investigation, multi-wall carbon nanotubes (MWCNT) with various percentages (0.6%, 1%, 1.4%, 2%) were combined into   ​and High-density polyethylene HDPE (60) wt. % and hydroxyapatite (40) wt. % to form biocomposite using hot-press techniques. The surface topography by AFM images illustrates differences in the roughness of the sample's surface with different adding percentages of MWCNT. The DSC technique exhibits the effect of adding MWCNT in different percentages with the degree of crystallinity, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…5 (d), (f) and (g) FE-SEM image clari es that bio-composite microstructures were homogeneous which will have an effect in enhancing the mechanical properties. Additionally, the FE-SEM with high magni cation image of the composite includes pores in the surface structure that allow bone intercellular to link when the bone cement is immersed in body [49].…”
Section: Surface Structure Resultsmentioning
confidence: 99%
“…5 (d), (f) and (g) FE-SEM image clari es that bio-composite microstructures were homogeneous which will have an effect in enhancing the mechanical properties. Additionally, the FE-SEM with high magni cation image of the composite includes pores in the surface structure that allow bone intercellular to link when the bone cement is immersed in body [49].…”
Section: Surface Structure Resultsmentioning
confidence: 99%
“…The mechanical effects of CNTs have been greatly noticed and used in applications such as medical, 161,162 pharmaceutical, 163 wound dressings, 164 various industries (namely aerospace, nano, and optics [165][166][167][168] ), strengthening of electrical devices, 169,170 and tissue engineering. 27 In tissue engineering, the appearance of the materials used, which originate from their mechanical traits, plays an important role.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…26 Abundant evidence has shown that mechanical stress, together with other physical factors, may remarkably augment the biosynthetic activity of cells in biosynthetic matrices. 27,28 Although strength and work at failure both dene the mechanical reliability of biomaterials, the elastic modulus is remarkably related to cellular material interactions. For example, the increase in Young's modulus can be calculated from the linear part of the stress-strain curve, which was used to analyze the stiffness of a cryogel aer it was blended with CNTs in a compression test for skeletal card tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in vitro is effective as the first stage of biocompatibility estimations. [38] So many invitro studies are concerned with biocompatibility features investigations [39][40][41][42][43][44][45][46][47] for bone substitute materials applications. However, in vivo investigations provide a better approximation of human conditions.…”
Section: Bone Substitute Materialsmentioning
confidence: 99%
“…[7] There is a developing need for synthesizing biomaterials for bone healing or replacement due to osteoporosis, bone cancer, and bone fracture. [8] Tissue engineering is regarded as an alternative method for repairing bone defects. In standard tissue engineering techniques, a template that works as a bridging material is called a scaffold.…”
Section: Introductionmentioning
confidence: 99%